Bartonella gene transfer agent: Evolution, function, and proposed role in host adaptation. (9th July 2019) - Québatte, Maxime; Dehio, Christoph
Abstract: The processes underlying host adaptation by bacterial pathogens remain a fundamental question with relevant clinical, ecological, and evolutionary implications. Zoonotic pathogens of the genus Bartonella constitute an exceptional model to study these aspects. Bartonellae have undergone a spectacular diversification into multiple species resulting from adaptive radiation. Specific adaptations of a complex facultative intracellular lifestyle have enabled the colonisation of distinct mammalian reservoir hosts. This remarkable host adaptability has a multifactorial basis and is thought to be driven by horizontal gene transfer (HGT) and recombination among a limited genus‐specific pan genome. Recent functional and evolutionary studies revealed that the conserved Bartonella gene transfer agent (BaGTA) mediates highly efficient HGT and could thus drive this evolution. Here, we review the recent progress made towards understanding BaGTA evolution, function, and its role in the evolution and pathogenesis of Bartonella spp. We notably discuss how BaGTA could have contributed to genome diversification through recombination of beneficial traits that underlie host adaptability. We further address how BaGTA may counter the accumulation of deleterious mutations in clonal populations (Muller's ratchet), which are expected to occur through the recurrent transmission bottlenecks during the complex infection cycle of these pathogens in their mammalian reservoir hosts and arthropod vectors.